The Effect of Net Profit Margin and Debt to Equity Ratio on Profit Growth - Dian Melisa; R Taufik Hidayat (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2025)
Purpose – This study aims to determine the effect of net profit margin and debt to equity ratio on profit growth. Design/methodology/approach – This research uses quantitative data, the sample in this study is profit growth sub sector banks which are listed on the Indonesia Stock Exchange in the period 2017 – 2022 as many as 12 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings – The results of this study indicate that the net profit margin variable has a positive and statistically insignificant effect on profit growth, the debt to equity ratio variable has a positive and statistically insignificant effect on profit growth. Research limitations/implications – This research hopes to provide information regarding profit growth and can provide benefits in decision making and can be used as reference material for further research.